Impact of Intracoronal Dentin Treatment Prior to Bleaching on Bond Strength of Restorative Materials - Zanconato-Carvalho,Erica Moreno (2014)
Surface treatment of dentin before the bleaching procedure may affect its permeability and influence the bond strength of restorative materials. This study evaluated the influence of surface treatment before the bleaching on shear bond strength (SBT) of restorative materials to intracoronal dentin. Dentin slabs were subjected to surface treatment: no bleaching (control - CON), no surface treatment + bleaching (HP), 37% phosphoric acid + bleaching (PA) and Er:YAG laser + bleaching (L). After the bleaching procedure, specimens (n=10) were restored with: microhybrid composite resin (MH), flowable composite resin (F), and resin-modified glass-ionomer cement (RMGIC). The shear test was carried out. ANOVA and Tukey's test (α=0.05) showed significant difference for surface treatment and restorative materials (p<0.05). CON presented higher STB and was statistically different from HP (p<0.05). PA and L showed intermediate values and were statistically similar to CON and HP (p>0.05). STB for MH and F were higher than RMGIC (p<0.05), and did not differ from each other (p>0.05). The surface treatments with phosphoric acid and Er:YAG laser before the bleaching procedure provided shear bond strength at the same level of unbleached dentin and the composite resins presented superior bond strength to the intracoronal dentin.